Evaluation of Librarian Perception Toward the Performance of SMAN 1 Way Jepara Library Services - Rizka Pitri; Ermi Cahyani (Jurnal El-Pustaka, 2025)
The library is a key component in supporting the teaching and learning process at schools, including SMAN 1 Way Jepara. The quality of library services can be assessed through five indicators: tangibles, reliability, responsiveness, assurance, and empathy. However, field observations revealed damaged book collections, a lack of variety in available materials, and low responsiveness from librarians. Previous studies have focused only on librarian attitudes, without evaluating the overall service quality. Based on these issues, this study aims to evaluate user perceptions of the library services at SMAN 1 Way Jepara. A descriptive quantitative method was used with 295 respondents as the sample. The findings show that users have a positive perception of the library services. This is reflected in the average scores for each indicator: tangibles (3.21), reliability (3.26), responsiveness (3.10), assurance (3.20), and empathy (3.25), all of which fall into the "agree" category. Thus, the library services are considered satisfactory by its users.